An Analysis of Connotative Meaning in the Subtitle of Capciptop! Short Movie - Rita Harisma; Vivin Agustin (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2022)
This research focuses on analysing the connotative meaning contained in Capciptop! Short Movie by using Chaers theory (1994). The objective of this research is to find out connotative meaning in the subtitle of a movie. The problems of the study are what are the connotative meaning and the kinds of connotative meaning in the subtitle of CapCipTop! short movie. This research used descriptive qualitative method because the data are in the form of the subtitle. Documentary analysis was applied to find out the connotative meaning contained in the subtitle of short movie. The researcher collected the data by downloading the short movie, watching it, and making a list of the utterances that contain connotative meaning. The result of the research shows that there are 9 utterances containing connotative meanings in the short movie. There are three kinds of connotative meaning found there; two positive connotations, one neutral connotations, and six negative connotations. Thus, the most connotative that used in the data are negative connotation. The connotations used in the short movie are to portray images and build certain atmospheres. The connotations found in the short movie play an important role in creating particular senses and delivering the messages.